High-redshift radio galaxy searches with the MeerKAT Galaxy Cluster Legacy Survey - Cossa, Vasco Salvador (Rhodes University, 2026)
We present the results of a search for high-redshift radio galaxy (HzRG) candidates using 30 of the 115 cluster fields of the MeerKAT Galaxy Cluster Legacy Survey (MGCLS). These fields were selected for their good dynamic range, astrometric accuracy, and full optical and infrared coverage from the Dark Energy Camera Legacy Survey (DECaLS) and the All-sky Wide Infrared Survey Explorer (AllWISE), respectively. Using multiwavelength data and in-band radio spectral index measurements, we find 777 HzRG candidates, and an additional 1,040 faint sources lacking spectral data as potential candidates. Together, these 1,817 candidates represent 0.91% of the full sample. We obtained complete spectral coverage for all sources above 0.76 mJy and complete spectral index measurements down to 30 μJy, probing the faintest GHz-frequency population ever targeted in HzRG searches to date. Taking advantage of in-band spectral index measurements produced in this study, we also investigate the limitations of the assumption of the literature’s canonical synchrotron spectral index α = −0.7 for inter-frequency flux density extrapolation. Using both the canonical spectral index and our in-band spectral index measurements, we compared the flux densities for MGCLS point sources extrapolated to three different frequencies in different signal-to-noise ratios (SNR), relating to existing radio large-area sky surveys at 100 MHz, 400 MHz, and 1 GHz away from the MGCLS centre frequency, respectively. Although the assumption α = − 0.7 did not have any effect at the 100 MHz separation, it introduced a 7% deviation at 400 MHz frequency separation for high SNR sources and overestimated flux densities by a factor of 4 for the 1 GHz frequency separation. These results demonstrate that relying on the canonical spectral index for flux density extrapolation is only reliable for frequency offsets below 400 MHz and not reliable for frequency offsets around 1 GHz, even at high SNR, reinforcing the importance of using measured in-band spectral indices for reliable low-frequency flux density extrapolations.
Keywords: Radio galaxies (http://id.loc.gov/authorities/subjects/sh99004096); Red shift (http://id.loc.gov/authorities/subjects/sh85112092); Expanding universe (http://id.loc.gov/authorities/subjects/sh85046408); MeerKAT (https://www.wikidata.org/wiki/Q6807657)